Analisis Implementasi Kebijakan Penanganan Pedagang Kaki Di Kota Bandar Lampung (Studi di Pasar Bambukuning Bandarlampung) - Sudarman Mersa (PUBLICA, 2011)
Street vendors and the city are like two sides of the coin. The existence of that one will always be followed by another presence. However, the city government would always consider street vendors as a virus of development that must be eradicated. This is the dilemma faced by the existence of street vendors. However, there are some municipalities can collaborate with street vendors to build the city in accordance with the vision and mission as well as friendly to the environment. Bandar lampung city government also has a hope for street vendors to continue its activities, without disturbing the beauty and cleanliness of the city. Various policies have been issued by the government of Bandar Lompung city , however the appeared street vendors problems, so far, have not been solved propery.